Effect of Span-80 and ultrasonication on biodesulphurization of lignite by Rhodococcus erythropolis: Lab to semi-pilot scale tests. (April 2018) - Mishra, Srabani; Akcil, Ata; Panda, Sandeep; Tuncuk, Aysenur
Highlights: R. erythropolis studied for Lignite biodesulphurization from lab to semi-pilot scale. Effect of Span-80 and Ultrasonication compared for enhanced biodesulphurization. Lab scale optimum parameters investigated for pilot scale efficiency using Span-80. 2% (v/v) Span80 proved beneficial with 51.2% biodesulphurization at 10L scale. Characterization studies provided better insights into the overall process. Abstract: Turkey is a country with vast lignite reserves, which can serve as a potential source of energy to meet the rising energy demands. However, the sulphur present in coal delimits its application in several sectors. Recently, various techniques have emerged for sulphur removal from coal. In the present study, the efficacy of Rhodococcus erythropolis DSM 44308 towards biodesulphurization of a Turkish lignite (TL) sample has been studied. Additionally, the effects of ultrasonication and surfactant, Span 80 (S80), on biodesulphurization of the lignite sample have been studied and compared. Optimum parameters obtained through shake-flask experiments have been considered for further scale up in laboratory (1L) and semi-pilot (10L) bioreactors. To the best of our knowledge, the biodesulphurization approach indicated in the present study using R. erythropolis is being reported for the first time. The study revealed that a maximum desulphurization of 44.6% was achieved in shake-flask experiment using Span 80 concentration of 2% v/v. In the scale up bioreactor studies, 49.2% and 51.2% sulphur removal was achieved in 1L and 10L bioreactors respectively. The ultrasonication technique (upto 1 h treatment) was observed to have a marginal effect, leading to only 6% enhancement in biodesulphurization when compared with the control. Mineralogical analysis of original and treated samples provided better insights into the structural and phase changes following microbial treatment in presence and absence of Span-80.